Medicinal Herbal Extracts: Therapeutic Potential in Acute Lung Injury - Jae-Won Lee; Hee Jae Lee; Seok Han Yun; Juhyun Lee; Hyueyun Kim; Ha Yeong Kang; Kyung-Seop Ahn; Wanjoo Chun (Future Pharmacology)
Acute lung injury (ALI) is induced by pneumonia, sepsis and other conditions. The disease characteristics include severe lung inflammation, in which various cells, such as epithelial cells, macrophages, and neutrophils, play a pivotal role. Corticosteroids and antibiotics are used to treat ALI; however, they may have side effects. Cumulative data confirm that traditional herbal medicines exert therapeutic effects against endotoxin-induced inflammatory responses in both in vitro and in vivo ALI studies. This review briefly describes the anti-ALI effects of medicinal herbal extracts (MHEs) and their molecular mechanisms, especially focusing on Toll-like receptor 4/nuclear factor kappa B cell pathways, with a brief summary of in vitro and in vivo ALI experimental models. Thus, the present review highlights the excellent potential of MHEs for ALI therapy and prevention and may also be useful for the establishment of in vitro and in vivo ALI models.